2019
DOI: 10.1021/jacs.9b09493
|View full text |Cite
|
Sign up to set email alerts
|

Well-Defined Silica-Supported Tungsten(IV)–Oxo Complex: Olefin Metathesis Activity, Initiation, and Role of Brønsted Acid Sites

Abstract: Despite the importance of the heterogeneous tungsten-oxo based olefin metathesis catalyst (WO 3 /SiO 2) in industry, understanding of its initiation mechanism is still very limited. It has been proposed that reduced W(IV)-oxo surface species act as precatalysts. In order to understand the reactivity and initiation mechanism of surface W(IV)-oxo species, we synthesized a well-defined silica-supported W(IV)-oxo species (≡SiO)WO(OtBuF 6)(py) 3 (OtBuF 6 = OC(CH 3)(CF 3) 2 ; py = pyridine) (F6@SiO 2-700) via Surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(63 citation statements)
references
References 57 publications
(139 reference statements)
7
56
0
Order By: Relevance
“…6a) was characterized by spectroscopic techniques (IR, NMR, and EXAFS) and shown to initiate metathesis in the presence of Lewis acids like B(C 6 F 5 ) 3 for all types of olens, including those without allylic C-H bonds, suggesting the opening of alternative and/or additional initiation mechanisms in the supported system. 164 Investigation of this system on silica supports prepared at different dehydroxylation temperatures shows that the rate of metathesis for olens having no allylic C-H bond increases with increasing amounts of residual OH groups, while olens having allylic C-H bonds do not show such behaviour (Fig. 6b), suggesting that surface protons can also be involved in the initiation, similar to what was suggested earlier for supported Mo metathesis catalysts.…”
Section: Understanding Classical Metathesis Catalysts Via Somc-bridgisupporting
confidence: 81%
See 2 more Smart Citations
“…6a) was characterized by spectroscopic techniques (IR, NMR, and EXAFS) and shown to initiate metathesis in the presence of Lewis acids like B(C 6 F 5 ) 3 for all types of olens, including those without allylic C-H bonds, suggesting the opening of alternative and/or additional initiation mechanisms in the supported system. 164 Investigation of this system on silica supports prepared at different dehydroxylation temperatures shows that the rate of metathesis for olens having no allylic C-H bond increases with increasing amounts of residual OH groups, while olens having allylic C-H bonds do not show such behaviour (Fig. 6b), suggesting that surface protons can also be involved in the initiation, similar to what was suggested earlier for supported Mo metathesis catalysts.…”
Section: Understanding Classical Metathesis Catalysts Via Somc-bridgisupporting
confidence: 81%
“…In order to further understand the formation of alkylidenes from the putative M(IV) oxo species, tailored W(IV) oxo complexes, [WO(OR) 2 (py) 3 ] (R ¼ Si(OtBu) 3 , tBu F 6 , and tBu F 9 ), and the corresponding well-dened supported [(^SiO) WO(OtBu F 6 )(py) 3 ] were synthesized as molecular and supported model systems, respectively. 163,164 With the molecular system, it was shown that addition of tris(pentauorophenyl)borane (B(C 6 F 5 ) 3 ) or alternative Lewis acids was essential to switch on metathesis activity for olens containing allylic C-H bonds, though interestingly no metathesis activity was observed for olens without allylic C-H bonds.…”
Section: Understanding Classical Metathesis Catalysts Via Somc-bridgimentioning
confidence: 99%
See 1 more Smart Citation
“…These Brønsted acid sites are most likely attributed to OH-group in close proximity to cationic Mo-sites as recently discussed for the related silica-supported W-oxo system. [39] Regarding the 13 C DNP-SENS spectrum of Mo=CHR + @SiO2-700 with pre-adsorbed Py (Fig. 4d), besides the signals of Py (147, 136 and 126 ppm) and TCE (75 ppm), these at 20, 130, 142 and 324 ppm are consistent with the presence of the cationic Mo alkylidenes, in view of their similar chemical shift with the molecular compound.…”
Section: Mo=chr + @Sio2-700mentioning
confidence: 66%
“…4,5 These support materials, most commonly silica (SiO 2 ) and alumina (Al 2 O 3 ), play a crucial role in stabilizing and site-isolating reactive intermediates on the surface. [6][7][8][9][10][11] While this strategy has been leveraged to great effect, the chemical properties of the support are seldom employed to modulate catalyst reactivity, despite the fact that the surface occupies the inner-coordination-sphere for single-site catalysts, and therefore plays an intimate role in determining the electronic properties of the catalyst. The treatment of supports as chemically dynamic ligands, as opposed to highsurface-area dispersants would allow for the application of lessons learned from the homogeneous catalysis literature, unlocking unique reactivity.…”
mentioning
confidence: 99%